First record of occurrence of Epiphragmophora estella (d’Orbigny, 1837) (Mollusca, Gastropoda, Stylommatophora) in Argentina - Cuezzo, Maria Gabriela (2014)
This is the first record of Epiphragmophora estella in Argentina, a species traditionally of Bolivian distribution. Specimens were found during several field trips conducted in the northern patch of the Southern Andean Yungas forest of Salta. Morphometrics and qualitative shell characters are described in order to validate the taxonomic identification. Current species distribution is also reported.